Validation of Suitable Reference Genes for Assessing Gene Expression of MicroRNAs in Lonicera japonica - Wang, Yaolong; Liu, Juan; Wang, Xumin; Liu, Shuang; Wang, Guoliang; Zhou, Junhui; Yuan, Yuan; Chen, Tiying; Jiang, Chao; Zha, Liangping; Huang, Luqi (Frontiers in Plant Science, 2016)
MicroRNAs (miRNAs), which play crucial regulatory roles in plant secondary metabolism and responses to the environment, could be developed as promising biomarkers for different varieties and production areas of herbal medicines. However, limited information is available for miRNAs from Lonicera japonica, which is widely used in East Asian countries owing to various pharmaceutically active secondary metabolites. Selection of suitable reference genes for quantification of target miRNA expression through quantitative real-time (qRT)-PCR is important for elucidating the molecular mechanisms of secondary metabolic regulation in different tissues and varieties of L. japonica. For precise normalization of gene expression data in L. japonica, 16 candidate miRNAs were examined in three tissues, as well as twenty-one cultivated varieties collected from sixteen production areas, using GeNorm, NormFinder, and RefFinder algorithms. Our results revealed combination of u534122 and u3868172 as the best reference genes across all samples. Their specificity was confirmed by detecting the cycling threshold (Ct) value ranges in different varieties of L. japonica collected from diverse production areas, suggesting the use of these two reference miRNAs is sufficient for accurate transcript normalization with different tissues, varieties, and production areas. To our knowledge, this is the first report on validation of reference miRNAs in honeysuckle (Lonicera spp.). Restuls from this study can further facilitate discovery of functional regulatory miRNAs in different varieties of L. japonica.